B36 Analysis of cholesterol biosynthetic pathway in huntington's disease. (13th September 2016) - Russo, Cinzia Valeria; Michele, Giuseppe de; Salvatore, Elena; Maio, Luigi Di; Peluso, Silvio; Massarelli, Marco; Roca, Alessandro
Abstract : Background: Molecular and biochemical studies in cellular and animal models have shown that cholesterol biosynthesis is altered in Huntington's disease (HD). A reduction in activity of cholesterol synthetic pathway with subsequent decline in the formation of cholesterol precursors such as lanosterol and lathosterol and levels of the brain-specific catabolite 24S-hydroxycholesterol was described. Htt toxicity and transcriptional alteration might further contribute to the observed alteration by reduced activity of SREBP that regulate the genes transcription of cholesterol biosynthetic pathway. To our knowledge no study has evaluated the cholestenoic acid profile of HD patients and investigated the role of Liver X Receptors which also regulate cholesterol metabolism. Aims: To evaluate the role of nuclear transcription factors related to cholesterol metabolism such as LxR we test whether there is alteration of natural ligands of LxR levels ( oxysterols and colestenoic acids) in HD patients compared to controls and evaluate gene expression of LxR and LxR target genes. Methods: Twenty-eight patients with clinically and genetically documented HD were included in the study and matched by age, sex, and BMI with 28 healthy control subjects. Clinical assessment of patients was performed using the UHDRS and TFC. Metabolic and molecular investigations included assays of triglyceride, total cholesterol, LDL, and HDL cholesterol; plasma lanosterol, lathosterol, desmosterol, 24-HC, 27-HC, 3β-HCA, 3β, 7α-diHCA, 3β, 7β-diHCA measured by gas chromatography mass spectrometry; mRNA extraction from blood samples and primary fibroblast cells isolated from HD patients and controls; analysis of the expression levels of LxR α-β, ABCG1, ApoE and SREPB genes by real time PCR. Results: Metabolic assessment showed no significant differences except for lower HDL patient levels. No significant differences in gene expression were observed in 13 patients than in 13 controls. No correlation between gene expression and UHDRS and TFC were observed. Conclusions: We have reported partial analysis of our study group. These preliminary data do not suggest a potential role of mutant Htt to regulate LxR and LxR-targeted genes. Nonetheless we cannot exclude that the increase of the sample and analysis of oxysterols and cholestenoic acids may give different results.